Réponses

2014-04-25T15:50:41+02:00
 A) I= x^{2} +2×x×5+5²-(x×7+x×(-2x)-5×7-5×(-2x) )
    I= x^{2} +10x+25-(7x-2 x^{2} -35+10x)
    I= x^{2} +10x+25-7x+2 x^{2} +35-10x
    I= x^{2} +2 x^{2} -7x+60

B) I=(x-5)(x-5)-(x-5)(7-2x)
     I=(x-5)[(x-5)-(7-2x)]
     I=(x-5)[(x-5)(-7+2x)]
     I=(x-5)(x×(-7)+x×2x-5×(-7)-5×2x)
     I=(x-5)(-7x+2 x^{2} +35-10x)
     I=(x-5)(2 x^{2}  -17x+35)

Merci beaucoup, tu me sauves beaucoup déjà, mais tu ne sais pas pour le c et d ? :)) !!!
non dsl
Pas grave, merci beaucoup ;)
derien :)